Sportmedizin im Wandel - Greier K; Ressle L (Dynamic Media Sales Verlag, 2012)
The sensorimotoric feedback performance of obese children and juveniles has been subject of scientific analysis in a very limited way. Studies show that normalweight children score higher as intensity increases when testing general motor skills, but there are hardly any results on sensorimotoric feedback performance up to now. The aim of this study is to compare the static and dynamic balance of obese and normal-weight school children. Materials and Methodology: Obese school children (BMI>97. percentile) ages 11 to 15 (n=20) from an obesity rehabilitation centre were tested using a sensorimotoric feedback device and the results were compared to the results of a control group (n=67) of normal-weight school children of the same age. Results: The test group of obese school children achieved significantly lower (p<0.05) scores on tests for static and dynamic balance compared to the control group. Normal-weight school children: Total score 65071 (SD); obese school children: Total score 49290 (SD). Conclusion: The low results of obese school children and juveniles on static and dynamic balance show the necessity of a specific and individual movement program for obese children in order to counter the existing deficits that may cause restrictions in their everyday life.Key Words: Balance, sensorimotoric Feedback Performance, obesity, school